Regional Determinants of German FDI in the Czech Republic - Evidence from a gravity model approach - Johannes Schäffler; Veronika Hecht; Michael Moritz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
On the basis of a unique dataset the regional distribution of German multinationals and their Czech affiliates is analysed for both countries. The investigation covers market size and agglomeration features, distance issues, and labour market characteristics. Apart from the vital role of large markets and a low transport distance there are further crucial findings regarding joint foreign direct investment (FDI) projects that can be revealed from a home-host country perspective: the strong position of the common border region, the non-relevance of a relatively high wage gap between the site of the headquarters and the location of the affiliate in coincidence with the great importance of the availability of high-skilled employees in the target country, and differences in the significance of sectoral employment shares.
Keywords: F15; F23; R12; 330